A day in the life of a psychiatrist in 2050: reflections on the inaugural Praxis trainees' section editorial competition. (June 2020) - Bailey, Cate
Summary: The Praxis trainees' section editor reflects on the inaugural editorial competition, celebrates the winner and shortlist, and shares her own forecast for psychiatry in 2050.